Mechanical Behavior of Piles in Typical Unsaturated Expansive and Collapsible Soils Upon Water Infiltration - Liu, Yunlong; Vanapalli, Sai K.; Jiang, Shipeng (Frontiers in Built Environment, 2022)
Pile foundations are widely used in all types of soils including expansive and collapsible soils that are typically found in nature in a state of unsaturated condition. Opposite trends in volume change behavior is typically observed when water infiltrates into expansive and collapsible soils. The design of pile foundations in these soils are conventionally based on saturated soil mechanics assuming drained conditions ignoring the influence of unsaturated conditions. In this study, infiltration tests were performed on two model piles; one of these piles is tested in an expansive soil and the other in a collapsible soil. The focus of this study is to determine the pile mechanical behavior including pile head load - displacement response, pile axial force, shaft friction and pile base resistance taking account of suction changes associated with water infiltration. The pile mechanical behavior is significantly influenced due to changes in the pile shaft friction in both expansive and collapsible soils. The response of the pile mechanical behavior variations were explained extending the concepts of unsaturated soil mechanics. The results of this study provide valuable information for the practicing engineers to gain a more comprehensive understanding of mechanical behaviors of pile foundations in expansive soils and collapsible soils upon water infiltration.